2000
DOI: 10.2188/jea.10.42
|View full text |Cite
|
Sign up to set email alerts
|

Exposure to Japanese Cedar Pollen in Early Life and Subsequent Sensitization to Japanese Cedar Pollen.

Abstract: The effect of exposure to Japanese cedar pollen (JCP) in early life on subsequent sensitization to it was evaluated. Specific IgE antibody to JCP was examined in 440-504 school children in a rural town each year during 1995-98. The amount of dispersed pollen measured by a Durham sampler widely ranged from 165 to 5941 grains/cm2/year during this period. The amount had been measured during the period of 1982-91 in which these children were born, and it also widely ranged from 148 to 8566 grains/cm2/year. Childre… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
10
0

Year Published

2004
2004
2016
2016

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 9 publications
(10 citation statements)
references
References 9 publications
0
10
0
Order By: Relevance
“…34 Cedar pollen sensitization and allergic airway symptoms (termed cedar pollinosis) appeared to have a "cohort effect" in which the younger generations had a higher prevalence of pollinosis, possibly stemming from high exposures in early life which corresponded well with the environmental load. 35,36 Aeroallergen sensitization patterns in Africa, Europe and the Americas Different patterns of aeroallergen sensitization were seen in other parts of the world ( Table 2). [37][38][39][40][41][42][43][44][45][46][47] In West Africa (Nigeria and Ghana), high prevalences of cockroach sensitization were seen in asthmatic children and adolescents, and cat dander was also a more significant allergen than in Asia.…”
Section: Aeroallergen Sensitization Patterns In Asian Countriesmentioning
confidence: 99%
“…34 Cedar pollen sensitization and allergic airway symptoms (termed cedar pollinosis) appeared to have a "cohort effect" in which the younger generations had a higher prevalence of pollinosis, possibly stemming from high exposures in early life which corresponded well with the environmental load. 35,36 Aeroallergen sensitization patterns in Africa, Europe and the Americas Different patterns of aeroallergen sensitization were seen in other parts of the world ( Table 2). [37][38][39][40][41][42][43][44][45][46][47] In West Africa (Nigeria and Ghana), high prevalences of cockroach sensitization were seen in asthmatic children and adolescents, and cat dander was also a more significant allergen than in Asia.…”
Section: Aeroallergen Sensitization Patterns In Asian Countriesmentioning
confidence: 99%
“…Several studies have documented the allergens/sensitizing agents and risk factors associated with the increased prevalence of AR and AR/C in the regions of interest .…”
Section: Pattern Of Allergens and Risks Associated With Allergic Diseasementioning
confidence: 99%
“…Although the very large diversity and overlapping types of grass, tree and weed pollen makes it virtually impossible to assign specific plants as the main causes of AR in the different regions, it does nevertheless appear that Salsola and other weed pollen are particularly important sensitizing agents in the Middle East , where as cereal pollen appear to be important sensitizers in Turkey . Although, a large number of studies from Japan suggest Japanese cedar pollen to be possibly the most prevalent and important sensitizing agents across Japan , other studies have indicated that Japanese birch and cypress pollen are also important in different parts of Japan . Similarly, there is some evidence that sensitization to the non‐traditional silk/silk worm allergens may be important in the aetiology of AR particularly in China and Japan .…”
Section: Pattern Of Allergens and Risks Associated With Allergic Diseasementioning
confidence: 99%
“…Many investigators found that the incidence of pollenosis is high in individuals born in autumn or winter and low in those born in spring [15][16][17][18][19][20][21]. Although the cause of this phenomenon has not yet been clarified, the exposure to pollens before 6 months old is regarded as playing a critical role [20,21]. On the other hand, it is also noted that the incidence of AD is higher in infants born in autumn and winter in western countries as well as in Japan [22][23][24][25].…”
Section: Discussionmentioning
confidence: 99%